Does economic sectorial diversification affect the relationship between carbon emissions, economic growth, energy consumption, coal and gas consumption? Evidence from OPEC countries using panel cointegration analysis - Moutinho, Victor (2022)
This work aims to investigate a relationship between economic and environmental drivers under the economic diversification condition including seven economic activity sectors for a set of nine OPEC countries during 1974–2016. For validating the two Environmental Kuznets Curve – EKC – equations proposed, a panel data analysis was followed through the long and short-run estimations, including the Pooled Mean Group, Mean Group, and Dynamic Fixed Effect estimators. Results of the cointegration panel estimators show, for some sectors the validity of the EKC in the form of an inverted U shape, alternating with the U-shaped form. Namely, sector 2 of the extractive and manufacturing industries, including the electricity, gas, and water industries, and sector 5, including wholesale, lodging, restoration, and similar activities, validate the EKC hypothesis. However, the validity of the Kuznets curve with the panel data does not make it clear which OPEC countries are in the most favorable conditions to mitigate the polluting effects.